2023
DOI: 10.3390/su151511998
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Critical Factors Impacting Hotel Online Ratings: A Comparison of Religious and Commercial Destinations in Saudi Arabia

Abstract: User-generated online ratings have become a prominent tool for hotels to enhance overall customer satisfaction. Prior research on online ratings has mainly considered commercial destinations, whereas research on religious destinations is limited. This study uses the IPA technique and beta regression analysis to investigate the destination’s (commercial and religious) varying effects on the relationship between hotel service quality attributes and customer satisfaction. In total, data from 338 hotels representi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 190 publications
0
2
0
Order By: Relevance
“…The result of this is shown in Table 3, with values for both the R-squared and adjusted R-squared. The results demonstrate a strong relationship between our model and the dependent variable [106,107]. It shows that approximately 76% of the variation in online grocery shopping (approximately 74% for adjusted R-squared) can be explained by the regions' median income, food prices, and mobile internet connection.…”
Section: Linear Regression Resultsmentioning
confidence: 62%
“…The result of this is shown in Table 3, with values for both the R-squared and adjusted R-squared. The results demonstrate a strong relationship between our model and the dependent variable [106,107]. It shows that approximately 76% of the variation in online grocery shopping (approximately 74% for adjusted R-squared) can be explained by the regions' median income, food prices, and mobile internet connection.…”
Section: Linear Regression Resultsmentioning
confidence: 62%
“…Li et al [18] identified the factors that influence hotel customer satisfaction through analyzing online reviews, and analyzed the importance of these factors and their relationship with customer satisfaction levels when booking luxury and economy hotels. Singh et al [19] compared the perceptions of different hotel service quality attributes among travelers in religious and commercial destinations, as well as the impact of these attributes on customer satisfaction. Alhamad and Singh [20] researched the significant and minor factors influencing online hotel ratings in consumer reviews to enhance online ratings and customer satisfaction.…”
Section: Introductionmentioning
confidence: 99%